Empowerment as a disabled, black woman - Oliver, Kym; Abdullahi, Jumoke (2020)
The dynamic duo of Jumoke and Kym tackle the topic of empowerment and what that means for disabled, Black women. This was filmed as part of a TEDx talk at the University of Sussex in England. _______________________________________________________________________________________________ TRIPLE CRIPPLES was created by @TheKymOliver & @JayOnLife to provide a platform for & highlight the narratives of Black & non-Black Women, Femmes & Non-Binary people of colour, living with disabilities. We are here. We exist! We know the media and mainstream disability conversations would have you believe otherwise mega eye roll*... But guess what? WE GOTS THA INTERNETS, BITCHEZZZZ!!! Eat it. *put on shades and look cool at night ———————————————————————————————- JOIN US ON OUR JOURNEY! Hit the comments box! And if you or any women/femmes/non-binary people you know, would like to be a guest... Hit the DM’s! 🖤 Website: https://thetriplecripples.uk/ Twitter/Instagram: @TripleCripples Follow Jumoke: @JayOnLife Follow Kym: @TheKymOliver ———————————————————————————————- Track: “runaway” ~ K15 feat. AMA LIVE! Big Love to K15 for kindly letting us use his amazing music as our bedding track!!! Check out @k15music, support his sound, buy some vinyls and follow him on all platforms: Twitter: @K15music Facebook: @K15music Soundcloud: @K15 Bandcamp: @K15music
Keywords: 2000 à aujourd'hui; afrique; amériques; approches et analyses; capacitisme; caraïbes; corps; cours; discours dominant; empowerment; europe; fem3300; femmes* noires; invisibilité; militance; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques